1990
DOI: 10.1002/ijc.2910450610
|View full text |Cite
|
Sign up to set email alerts
|

Changes in glycolipid expression in human testicular tumor

Abstract: Glycolipids were extracted from testicular tumor tissues of 13 patients, and their pattern of expression compared with that of normal testicular tissue. The most conspicuous and consistent change in the tumor extracts was marked accumulation of CTH (ceramide trihexoside). Structural analysis by enzyme cleavage showed that CTH which accumulated in the tumor tissue was Gb3 (Gal alpha 1-4Gal beta 1-4Glc beta 1-Cer). Immunohistochemistry using anti-Gb3 monoclonal antibody (MAb) (1A4) also indicated massive accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…Elevated expression of Gb 3 was also detected in astrocytoma cell lines (32) and in several highly metastatic types of human tumors, including ovarian and breast cancers (33). Significant Gb 3 accumulation was also previously reported in testicular seminoma, which correlated with the metastatic potential (34,35). These data support our finding that Gb 3 expression is a marker for colonic epithelial tumor cell transformation from primary cancer into the metastatic stage and indicate that several types of invasive tumors may have common mechanisms for metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…Elevated expression of Gb 3 was also detected in astrocytoma cell lines (32) and in several highly metastatic types of human tumors, including ovarian and breast cancers (33). Significant Gb 3 accumulation was also previously reported in testicular seminoma, which correlated with the metastatic potential (34,35). These data support our finding that Gb 3 expression is a marker for colonic epithelial tumor cell transformation from primary cancer into the metastatic stage and indicate that several types of invasive tumors may have common mechanisms for metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…The decisive requirement for application of STxB is the cellspecific expression of Gb 3 in tumor cells: Gb3 is expressed by Burkitt and centrofollicular lymphoma and solid tumors like testicular seminoma, breast, ovary, pancreatic, and colon cancer (5,6,8,(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, several groups have reported that the glycosphingolipid globotriaosyl ceramide (Gb 3 or CD77), like other glycosphingolipids (2,3), is expressed in human malignancies. Gb 3 expression has been shown in Burkitt's and centrofollicular lymphomas (4 -7), in a wide range of solid tumors such as breast and ovarian carcinomas (8,9), and in testicular seminomas (10). Moreover, it was recently reported that Gb 3 expression in human colorectal cancer correlates with invasiveness and the ability to form metastasis (11).…”
Section: Introductionmentioning
confidence: 99%